HUBUNGAN ANTARA TINGKAT PENDIDIKAN DAN POLA PEMBERIAN MAKANAN TAMBAHAN DENGAN STATUS GIZI PADA BALITA USIA 6 - 24 BULAN DI DESA GENTAWANGI KECAMATAN JATILAWANG KABUPATEN BANYUMAS - Suci Khasanah (Universitas Harapan Bangsa Purwokerto, 2015)
This research is know the relationship between maternal educational level and supplementary feeding pattern with nutritional status for infants in the age of6-24 months. The research method using observational analytic with designcross-sectiona l and simple random sampling technique sampling conducted in.The sample of this research are 54 respondents. Technique of data collectionusing questionnaires and form recall on 8 June until 1 July , 2011. Data analysisusing the spearman rank correlation test (rho). The results of the research with sothe relationship between maternal educational level with nutritional status forinfant in the age of 6-24 months and the relationship between the supplementaryfeeding pattern with nutritional status for infant in the age of 6-24 months at asignificance level of 5% found that the value p < 0.05 is 0.000. Based on theresults of the analysis, the researcher concluded that there is a significantrelationship between maternal educational level and supplementary feedingpattern for infants in the age of 6-24 months with nutritional status in Gentawangiof Jatilawang Subdistrcit of Banyumas Regency. Key words: Education, Pattern of Feeding, Nutritional Status In Toodler